The Implementation of Color Vowel Chart to Enhance the EFL Students’ Pronunciation At SMPN 1 Majauleng - Andi Mulyani Kone; Hariratul Jannah; Andi Hafzah (Fakultas Sastra - Universitas Muslim Indonesia, 2019)
This research aims to find out the color vowel chart in improving the second year students’ pronunciation of SMPN 1 Majauleng. The method of this research is pre-experimental method with two class pre-test and post-test design. The population of this research is the second year students of Color Vowel Chart in academic year 2017/2018, it consists of 40 students which divided in two classes. This research uses random samping and two class as the sample is ten class women VIII B and ten class Men VIII C. The result of the research indicates that there is a significant difference between pre-test and post-test where the mean score of pre-test is 78 and the mean score of post-test 85. It indicates that there is a significant difference before and after teaching by using color vowel chart method in students’pronunciation.